Azithromycin vs penicillin G benzathine for early syphilis: A meta‐analysis of randomized controlled trials. Issue 6 (26th August 2020) - Li, Yizhi; Jiang, Guan
Abstract: Syphilis is a very serious infection that causes acute cutaneous manifestations. Penicillin is the gold standard for treating syphilis. This meta‐analysis was conducted based on self‐published randomized controlled trials (RCTs) data to compare the efficacy of azithromycin with penicillin for treating syphilis. RCTs on azithromycin vs penicillin for the treatment of syphilis were retrieved from the Cochrane Library, MEDLINE, EBSCO, Embase, Ovid, and other databases, and the estimated risk ratio (RR) and 95% confidence interval (CI) were used to study the following outcome indicators: 3‐month response rate, 6‐month response rate, 12‐month response rate, recurrence rate, serum fixation rate, and failure rate. This meta‐analysis included seven RCTs involving 639 subjects (of whom 335 were treated with azithromycin and 304 were treated with penicillin). There was no significant difference in the 3‐month response rate (RR = 0.97, 95% CI: 0.79‐1.19), 6‐month response rate (RR = 1.01, 95% CI: 0.85‐1.20), 12‐month response rate (RR = 1.02, 95% CI: 0.97‐1.09), serum fixation rate (RR = 0.71, 95% CI: 0.24‐2.12), and failure rate (RR = 0.62, 95% CI: 0.33‐1.16). In summary, there is no evidence in the literature that azithromycin is less effective than penicillin for treating syphilis. Highlights: Clinically, there are more effective and suitable drugs for patients with penicillin allergy than penicillin G benzathine, which is the classic drug for treating syphilis. Azithromycin might be a good alternative to penicillin G benzathine for treating syphilis. We compared azithromycin vs penicillin for treating syphilis via randomized controlled trial data. The response rate and serum fixation rate of azithromycin are no worse than that of penicillin G benzathine.